2015
DOI: 10.1007/s00737-015-0554-8
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective sleep during pregnancy: links with depressive and anxiety symptoms

Abstract: The aims of this paper are to study the associations between objective and subjective sleep in pregnant women, to examine which specific aspects of women's sleep are associated with depressive and anxiety symptoms and to test the moderating role of depressive and anxiety symptoms in the relations between objective and subjective sleep. The sample included 148 pregnant women. Objective sleep was measured by actigraphy for five nights at the participants' home, and subjective sleep was measured with the Pittsbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 40 publications
2
32
1
5
Order By: Relevance
“…It has been reported that objectively measured sleep duration deviates from that reported by more than one hour in about a third of the study participants [38]. Further, a recent study assessed sleep quality during pregnancy using both questionnaires and actigraphy [39] and found that depressiveness and anxiety were related to self-reported sleep quality but not to objective measurements of poor sleep quality. This was interpreted to suggest that women with the highest level of emotional distress perceive fragmented sleep as more detrimental to their health than the other women.…”
Section: Limitations Of the Studymentioning
confidence: 89%
“…It has been reported that objectively measured sleep duration deviates from that reported by more than one hour in about a third of the study participants [38]. Further, a recent study assessed sleep quality during pregnancy using both questionnaires and actigraphy [39] and found that depressiveness and anxiety were related to self-reported sleep quality but not to objective measurements of poor sleep quality. This was interpreted to suggest that women with the highest level of emotional distress perceive fragmented sleep as more detrimental to their health than the other women.…”
Section: Limitations Of the Studymentioning
confidence: 89%
“…A relationship between prenatal depression and sleep quality in pregnant women has previously been demonstrated, showing that higher levels of prenatal depression predicted poorer sleep quality, as depression is one of the main psychological factors contributing to sleep complaints [7,14,34,35]. The association between poor sleep quality and depressed mood has also been shown in epidemiologic studies of sleep in the general population [36], and with postpartum women [37,38].…”
Section: Discussionmentioning
confidence: 92%
“…One study found a correlation between the severity of insomnia in the perinatal period and depression and anxiety symptoms in women (Swanson et al, 2011). Another study found that depression and anxiety symptoms caused sleep problems throughout pregnancy (Volkovich, Tikotzky, Manber, 2016). In yet another study, results showed that pregnant women with depression had difficulty in initiating and maintaining sleep (Ruiz-Robledillo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%